Determinan Kepatuhan Wajib Pajak Orang Pribadi dalam Pemenuhan Kewajiban Perpajakannya di Lembaga Pendidikan Yayasan Swasta Katolik - Masihaena Fau; Sarwani -; Kadir - (Universitas Trunojoyo Madura, 2018)
This study aimed to give empirical evidences about the effect of knowledge of taxes, taxes sanction, taxes service quality, and administration system/taxes policy to the taxpayer complience . The population in this study was 508 employees who are taxpayers in three catholic Private Education Foundations in Banjarmasin, Sibolga and Nias. The Foundations were Anawim, Santa Maria Bunda Berbelas Kasih and Santa Maria Gracia, The data were collected from the output of questionnaires which were given to the respondents. The sampling technique used purposive sampling with 251 samples.The results showed that there was a positive effect of knowledge of taxation, taxation sanctions and tax service quality on taxpayer compliance because of having knowledge but because they did not have the background in taxation knowledge and also strict taxation sanctions and good service quality affected taxpayer compliance in fulfilling their obligations while the administration system / tax policy does not affect the responsibility of the taxpayer because it directly does not feel the benefits directly and also feels it has been obedient because it has been cut directly by the treasurer so that it ignores the annual SPT report which is a WP obligation.